Age‐related rhesus macaque models of COVID‐19 - Yu, Pin; Qi, Feifei; Xu, Yanfeng; Li, Fengdi; Liu, Peipei; Liu, Jiayi; Bao, Linlin; Deng, Wei; Gao, Hong; Xiang, Zhiguang; Xiao, Chong; Lv, Qi; et al. (Animal models and experimental medicine, 2020)
Background Since December 2019, an outbreak of the Corona Virus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome coronavirus (SARS‐CoV‐2) in Wuhan, China, has become a public health emergency of international concern. The high fatality of aged cases caused by SARS‐CoV‐2 was a need to explore the possible age‐related phenomena with non‐human primate models. Methods Three 3‐5 years old and two 15 years old rhesus macaques were intratracheally infected with SARS‐CoV‐2, and then analyzed by clinical signs, viral replication, chest X‐ray, histopathological changes and immune response. Results Viral replication of nasopharyngeal swabs, anal swabs and lung in old monkeys was more active than that in young monkeys for 14 days after SARS‐CoV‐2 challenge. Monkeys developed typical interstitial pneumonia characterized by thickened alveolar septum accompanied with inflammation and edema, notably, old monkeys exhibited diffuse severe interstitial pneumonia. Viral antigens were detected mainly in alveolar epithelial cells and macrophages. Conclusion SARS‐CoV‐2 caused more severe interstitial pneumonia in old monkeys than that in young monkeys. Rhesus macaque models infected with SARS‐CoV‐2 provided insight into the pathogenic mechanism and facilitated the development of vaccines and therapeutics against SARS‐CoV‐2 infection.